Competition, complexity, and security design: evidence from retail investment products - Chesney, Marc; Fattinger, Felix; Krakow, Jonathan; Straumann, Simon (Review of Finance, 2026)
Abstract We investigate the role of strategic security design in the market for retail investment products. Focusing on a dominant yet understudied design feature, we provide evidence consistent with issuers’ strategic increase of product complexity to mitigate price competition. Complexity facilitates product differentiation, thereby impairing investors’ ability to compare products. Because more complex products entail greater markups, imply higher tail risk, and are first-order stochastically dominated by simpler products, the empirically observed rise in market complexity increases uncompensated risk-taking, particularly among less sophisticated investors. Overall, our findings indicate that complexity is shaped by issuers’ deliberate design choice to preserve product rents.